2022
DOI: 10.1002/adma.202107902
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Electronics and Devices as Human–Machine Interfaces for Medical Robotics

Abstract: Medical robots are invaluable players in non-pharmaceutical treatment of disabilities. Particularly, using prosthetic and rehabilitation devices with human-machine interfaces can greatly improve the quality of life for impaired patients. In recent years, flexible electronic interfaces and soft robotics have attracted tremendous attention in this field due to their high biocompatibility, functionality, conformability, and low-cost. Flexible human-machine interfaces on soft robotics would make a promising altern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
190
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 329 publications
(190 citation statements)
references
References 617 publications
(961 reference statements)
0
190
0
Order By: Relevance
“…Methods of interaction and communication between human beings and machines are becoming more effective due to fast progress in the area of human-machine interfaces (HMIs), 1,2 especially in dealing with the acceptance and transmission of physicochemical signals, physiological signals, communication signals, soft-robot driving, and feedback stimulation. HMI technology based on e-skin has developed rapidly since a sensory feedback system was first used in surgical operations to transmit patient physiological signals in 1974.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Methods of interaction and communication between human beings and machines are becoming more effective due to fast progress in the area of human-machine interfaces (HMIs), 1,2 especially in dealing with the acceptance and transmission of physicochemical signals, physiological signals, communication signals, soft-robot driving, and feedback stimulation. HMI technology based on e-skin has developed rapidly since a sensory feedback system was first used in surgical operations to transmit patient physiological signals in 1974.…”
Section: Introductionmentioning
confidence: 99%
“…3 Hydrogels, with the advantages of high ductility 4 and good self-healing properties, 5 can be used to allow e-skin to show high temporal and spatial resolution under varying degrees of strain and stress. Therefore, they are widely used in medical equipment to monitor the physiological signals of patients, 1,6 in touch devices to build reconfigurable touch panels, 7 to build triboelectric nanogenerators (TENGs), 8 etc. From a mechanical perspective, hydrogels used for HMIs must have sufficient stability to adapt to the unpredictable shapes of skin or mechanical interfaces, so as to eliminate motion artifacts and improve the accuracy of monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…Stretchable conductors with the combination of high elasticity and electric conductivity have long been pursued in soft electronics for applications in sensing, actuating, energy harvest, soft robotics, electronic skins, wearable, and biomedical devices. [1][2][3] In most of production procedure, solid conductive materials (e.g., metals, carbon, polyelectrolytes, conjugated polymers, and their nanomaterials) [4] were either deposited on or engineered sintering process of pressure trace. [10] Interestingly they showed that the conductive pathway could survive from cutting and puncturing, since structural damage may result in an external force and then sintered the LM droplets around the wounds.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the existing conventional electronic sensors, the flexible sensor has shown high biocompatibility and real-time monitoring, as well as further advantages. They are the most extensively utilized in human health monitoring and human-machine interaction [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] owing to their simple structural design, which converts physical motion, including compression, bending, tension, shear, stress, and strain, into electrical signals. These kinds of sensors can detect human quotidian activities, including joints and muscle movement, respiration, pulses, etc.…”
Section: Introductionmentioning
confidence: 99%